E-cycling intention versus behavioral change: Investigating longitudinal changes in e-cycling intention and actual behavior change in daily commuting - Joost de Kruijf; Dea van Lierop; Dick Ettema; Maarten Kroesen; Martin Dijst (Journal of Cycling and Micromobility Research)
By offering the opportunity to make longer trips at a lower level of physical activity, the e-bike provides a promising alternative to car use. Despite all advantages (e-)cycling brings to urban accessibility, the environment, physical and mental health, not all car commuters regard the e-bike as a suitable alternative yet in their daily activity patterns. This study reports on changes in behavioral intention and actual e-cycling brought about by an e-cycling incentive program in the province of Noord-Brabant, the Netherlands. The impact of the program on behavioral intention and the actual change to e-cycling were analyzed based on a longitudinal three-wave survey design on past, intended, and actual commuting behavior. To explore the changes in behavioral intentional, the differences between intention and actual behavior and the factors influencing them, descriptive and ordinal logistic regression analyses were conducted. To explore the dynamics between e-cycling intentions and behavior a longitudinal structural equation model was developed. In general, this study shows that the incentive program has a positive impact on participants’ behavioral change to e-cycling during the incentive program. Results show that two-third of the participants actually use the e-bike as much as they intended at the start of the program. People who were used to taking the conventional bicycle to work before the stimulation program, are more consistent between their intention and behavior. Results also show that personal beliefs, habits, and goal-related variables do not influence the intention–behavior consistency.